CONSTRUÇÃO DE POÇOS TUBULARES PROFUNDOS NA REGIÃO METROPOLITANA DE BELÉM - de Oliveira, Josafá Ribeiro; Centeno Júnior, Felisberto M.; Pontes, Manfredo Ximenes; Imbiriba Júnior, Manoel; Botelho, João Benedito da Silva (Águas Subterrâneas, 2000)
The urban and industrial expansion in the Metropolitan Region of Belém is imposing a large demand o ground-water and, consequently, is increasing the construction of deep wells as shown in the inventory elaborated by Companhia de Pesquisa de Recursos Minerais (CPRM), within the project Hydrogeological Studies of Metropolitan Region of Belém, in which were listed more than 60 deep tubular wells, from which 45 are still in operation , continuously, twenty four hours a day. The early drills are of the end of decade of 70, beeing CORNEA and CPRM, followed by FEMAC and HIDROENGE the pioneers. In the 90’s it was an increment in the number of drillings, specially in depths larger than 130 meters. In the drilling of these wells ,it was utilized rotary drills. The FEMAC GEOSOLO Engenharia Ltda. and HIDROENGE are leading the drillings with 60% and 40%, respectively, in the RMB. COSANPA works with 30 wells, furnishing approximately 9,000 m3/h of ground-water from 15 deep wells. There are 10 industrial deep wells, but, in lieu of lack of information, it was not possible to estimate the total volume exploited. With regard to constructive aspects, the method utilized is the rotary drilling with depths of about 280m and chambers of pumping between 12 and 14 inches. Almost all wells are reveted with schedulle 40 tube and with inox screen filters with 8 inches. In relation to pumping equipment, the wells ara adapted with submersible pumps Leão and Ebara, with capacity of 150 up to 300m3/h ; the total costs of ground-water wells ranging R 150,000 and R 170,000.